Effects of public-school choice on private schools: Evidence from open enrollment reform - Ricardo Meilman Cohn (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
This paper investigates the effect of a policy-induced increase in public school competition on private school enrollment and budget outcomes. I exploit a natural experiment created by the introduction of an open enrollment policy that expanded public school choice opportunities and increased competitive pressure on private schools. Using a new data set constructed from mandatory nonprofit information returns and school enrollment records, I find that an increase in public school competition reduces private school enrollment. Secular and Catholic school enrollment is most responsive to increased public school choice, whereas other Christian and other faith schools experience no reduction in enrollment. The negative enrollment effects are concentrated among high school age students. I find no evidence that private schools respond to this increased public school choice by adjusting their revenue and spending choices
Keywords: 330; school choice; school competition; open enrollment; private schools